2017
DOI: 10.18203/2320-6012.ijrms20174566
|View full text |Cite
|
Sign up to set email alerts
|

Serum acid phosphatase level - is it a marker for diagnosis of malaria

Abstract: Background: Malaria is endemic throughout most of the tropics. Technically, detection of malaria parasite may be missed due to low parasite density at sampling time and poor blood film preparation. The study was aimed to evaluate the serum acid phosphatase levels as a possible diagnostic marker for malarial infections.Methods: This study was conducted on a total of 100 subjects (40 malaria cases, 30 non-malarial cases and 30 sex and age matched healthy controls attending the department of medicine, PESIMSR, Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The study revealed that total protein levels decreased in malaria infected children when compared with non-infected children. This observation was consistent with the reports given by Wokem et al [9]; Devi et al [22].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The study revealed that total protein levels decreased in malaria infected children when compared with non-infected children. This observation was consistent with the reports given by Wokem et al [9]; Devi et al [22].…”
Section: Discussionsupporting
confidence: 94%
“…Comparing malaria infected children with the controls, decreased albumin levels were seen in malaria infected children. This finding is in accordance with the study of Wokem et al [13]; Devi et al [22]. The severity of malaria depends on an individual's initial immunity.…”
Section: Discussionsupporting
confidence: 93%